2008
DOI: 10.1021/ja076007z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Reactions between Neutral Vanadium Oxide Clusters and Ethane, Ethylene, and Acetylene

Abstract: Reactions of neutral vanadium oxide clusters with small hydrocarbons, namely C2H6, C2H4, and C2H2, are investigated by experiment and density functional theory (DFT) calculations. Single photon ionization through extreme ultraviolet (EUV, 46.9 nm, 26.5 eV) and vacuum ultraviolet (VUV, 118 nm, 10.5 eV) lasers is used to detect neutral cluster distributions and reaction products. The most stable vanadium oxide clusters VO2, V2O5, V3O7, V4O10, etc. tend to associate with C2H4 generating products V(m)O(n)C2H4. Oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(162 citation statements)
references
References 85 publications
6
154
0
2
Order By: Relevance
“…[19] The DFT calculations have been carried out using the Gaussian 09 program [20] employing the hybrid B3LYP exchange-correlation functional [21] with the unrestricted Kohn-Sham solution, [22] and TZVP basis sets. [23] The unrestricted B3LYP/TZVP level of theory proved reliable in previous studies of cationic, [24] anionic, [25] and neutral [10] AlVO 5 À , [27] V 2 SiO 8 À , [28] V 2 SiO 7 + , [11d] and V 3 PO 10 +[11a,c] and their gas-phase reactions with small alkanes. For the optimization of transition structures (TS), we employed either the Berny algorithm [29] or the synchronous transitguided quasi-Newton (STQN) method.…”
Section: /Ptomentioning
confidence: 69%
See 1 more Smart Citation
“…[19] The DFT calculations have been carried out using the Gaussian 09 program [20] employing the hybrid B3LYP exchange-correlation functional [21] with the unrestricted Kohn-Sham solution, [22] and TZVP basis sets. [23] The unrestricted B3LYP/TZVP level of theory proved reliable in previous studies of cationic, [24] anionic, [25] and neutral [10] AlVO 5 À , [27] V 2 SiO 8 À , [28] V 2 SiO 7 + , [11d] and V 3 PO 10 +[11a,c] and their gas-phase reactions with small alkanes. For the optimization of transition structures (TS), we employed either the Berny algorithm [29] or the synchronous transitguided quasi-Newton (STQN) method.…”
Section: /Ptomentioning
confidence: 69%
“…[9] In addition, the experimental observation and theoretical investigation of a neutral VO 3 radical bearing a V-O t C center have been reported by Bernstein and co-workers. [10] More recently, the groups of Schwarz and He described the efficient, thermal activation of methane by various stoichiometric binary oxide clusters containing M-O t C centers; [11] one interesting example concerns the thermal activation of methane by AlVO 4 + as proposed by Wang et al [11b] Surprisingly, the M-O t C center of AlVO 4 + is located on the maingroup metal Al but not on the transition-metal V. The thermodynamic and kinetic driving force of methane activation is indeed related to the properties of the Al-O t C moiety.…”
Section: /Ptomentioning
confidence: 99%
“…[10] For the latter system, aluminum oxide cluster cations that have an odd number of aluminum atoms and lack an oxygen-centered radical do not react with methane. [10,11] Further studies on the role of oxygen-centered radicals in chemical reactions showed that other substrates, such as ethylene or acetylene, can also be activated by different radical transition-metal oxide clusters, such as neutral VO 3 C. [12] Room-temperature hydrogen-atom abstraction from methane by a metal-free radical cation oxide was reported recently by de Petris et al [13] In this elegant experimental and computational study, it was demonstrated that [SO 2 ]C + brings about efficient activation of methane [Eq. (2)] with a rate…”
mentioning
confidence: 99%
“…B. durch neutrales VO 3 , aktiviert werden können. [12] Kürzlich berichteten de Petris et al über die Aktivierung von Methan bei Raumtemperatur durch Abstraktion eines Wasserstoffatoms, wobei erstmals ein metallfreies radikalisches Oxidkation eingesetzt wurde. [13] Durch eine elegante Kombination von experimentellen und theoretischen Untersuchungen konnten sie zeigen, dass [SO 2 ]C + eine effektive Aktivierung von Methan ermöglicht [Gl.…”
unclassified